Concomitant Therapy with Immunomodulator Enhances Infliximab Durability in Pediatric Inflammatory Bowel Disease. Issue 10 (October 2017) - Cheng, Julianna; Hamilton, Zachary; Smyth, Matthew; Barker, Collin; Israel, David; Jacobson, Kevan
Abstract : Background: Data on long-term durability of infliximab (IFX) and outcomes of concomitant therapy with immunomodulator in pediatric inflammatory bowel disease are limited. Methods: Children with inflammatory bowel disease who received IFX ± immunomodulator were retrospectively reviewed. Predictors of induction response were assessed using a binary logistic regression model and long-term outcomes evaluated by Cox proportional hazards model. Propensity score matching examined long-term efficacy of concomitant therapy in patients with Crohn's disease (CD). Results: Among 148 patients (113 CD, 35 ulcerative colitis; median age at IFX initiation 14.09 years [interquartile range 12.16–15.65]), 91% experienced response to induction therapy; patients with CD were more likely to respond (95% versus 77%, odds ratio = 2.63, 95% confidence interval, 1.01–6.85, P = 0.048). Despite dose optimization, secondary loss of response occurred at a rate of 9.01% and 8.33% per year for patients with CD and ulcerative colitis, respectively. A Cox proportional hazards model showed that concomitant therapy >6 months significantly lowered the risk of secondary loss of response in CD (hazard ratio = 0.39, 95% confidence interval, 0.17–0.88, P = 0.025). The same trend was observed in ulcerative colitis but did not reach significance. A higher proportion of patients on IFX monotherapy stopped IFX because of loss of response or infusion reactions (55% versus 21%, P < 0.001). Propensity score analysis of patients with CD showed significantly higher steroid-free remission rates for concomitant versus monotherapy at 1 year (78% versus 54%, P = 0.020) and 2 years (68% versus 46%, P = 0.044), and durability of response ( P = 0.022). Conclusions: These data demonstrate sustained efficacy of IFX in a cohort of pediatric patients with inflammatory bowel disease with durability of response enhanced by concomitant therapy. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 22 August 2017.